2021
DOI: 10.5483/bmbrep.2021.54.1.229
|View full text |Cite
|
Sign up to set email alerts
|

Hitting the complexity of the TIGIT-CD96-CD112R-CD226 axis for next-generation cancer immunotherapy

Abstract: Antibody-based therapeutics targeting the inhibitory receptors PD-1, PD-L1, or CTLA-4 have shown remarkable clinical progress on several cancers. However, most patients do not benefit from these therapies. Thus, many efforts are being made to identify new immune checkpoint receptor-ligand pathways that are alternative targets for cancer immunotherapies. Nectin and nectin-like molecules are widely expressed on several types of tumor cells and play regulatory roles in T- and NK-cell functions. TIGIT, CD226, CD96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 87 publications
2
41
0
Order By: Relevance
“…There is evidence for inhibitory functions of CD96, but the exact effect on human T-cells and NK cells is still not fully understood [ 19 ]. In human cancer, a correlation of CD96 with T-cell markers and PD-1 was shown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence for inhibitory functions of CD96, but the exact effect on human T-cells and NK cells is still not fully understood [ 19 ]. In human cancer, a correlation of CD96 with T-cell markers and PD-1 was shown.…”
Section: Discussionmentioning
confidence: 99%
“…Besides LAG-3 and Tim3, there are many other potentially therapeutically relevant immune checkpoints. T-cell immunoglobulin and ITIM domain (TIGIT) is a T-cell- and NK-cell-based inhibitory receptor [ 19 ]. The main TIGIT ligand, CD155, is expressed on tumor-infiltrating myeloid cells, macrophages and also tumor cells [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further combination strategy to enhance antitumor mAb-triggered NK cell functions relies on the blockade of immune checkpoint inhibitory receptors. PD-1 or TIGIT blockade was shown to augment trastuzumab and cetuximab therapeutic efficacy in preclinical models and progressed to clinical trials in patients with advanced malignancies [35][36][37][182][183][184][185]; combinations aimed at blocking other immune checkpoints expressed in NK cells are currently under study and may soon approach the clinic [186] (Table 1 and Figure 1).…”
Section: Strategies That Amplify Nk Cell Responsiveness To Cd16 Engagementmentioning
confidence: 99%
“…2,3 Among them, TIGIT (WUCAM, VSIG9, VSTM3), CD96 (TACTILE), and CD112R (PVRIG) are immunoreceptors in the nectin family that have been identified as important regulators of immune responses. [4][5][6] These co-inhibitory receptors are expressed on T and natural killer cells, and their blockade has shown enhanced anti-tumor immune responses. [7][8][9] However, it has also been reported that CD96 has co-stimulatory rather than co-inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%